How does the double-track human resource management model contribute to job burnout and mental health among Chinese government departments? A Chinese police study - Liang, Zhengyan; Yao, Min; Li, Hao; Chen, Jiayu; Yang, Mei; Tang, Tian; Ye, Hong; Zeng, Yuqing; Zhang, Minqiang (Frontiers in Public Health, 2024)
Objectives This study aims to investigate the contribution of the double-track human resource management model to the job performance and mental health of frontline police within China’s public security organs. Methodology An individual-centered approach, latent profile analysis (LPA), was utilized in this study, which used cluster sampling to survey all police of all 118 frontline police stations in an economically underdeveloped area of China and 839 personnel were selected for the analysis. This method allowed for a detailed examination of the contribution of the double-track system to job performance and mental health. Findings and conclusion The study identified three subtypes of job burnout among Chinese police: low job burnout, medium job burnout, and emotional exhaustion type. The double-track human resource management model in China’s public security organs has contributed to significant disparities between civilian and auxiliary police, such as more severe job burnout among civilian police, lower job performance, and mental health among auxiliary police. Implications To mitigate the potential risks associated with the double-track human resource management model, adjustments are necessary for both the management system and the treatment distribution system, which would also help address the disparities and improve the overall wellbeing and performance of all police officers.